‘Julius von Schlosser: aesthetics, art history and the book’, Report on the 150th Anniversary Conference on Julius von Schlosser, 6th and 7th October 2016: Julius von Schlosser (1866–1938), Internationale Tagung zum 150. Geburtstag, gemeinsam veranstaltet vom Kunsthistorischen Museum Wien und dem Institut für Kunstgeschichte der Universität Wien - Matthew Rampley (Journal of Art Historiography, 2016)
This report provides an overview of the main themes and questions explored at the conference held in Vienna on the 150th anniversary of the birth of Julius von Schlosser. It considers in particular his attempts to address the challenges presented by what he regarded as the primacy of the aesthetic artefact in art historical discourse. It presents the broader interests of Schlosser’s diverse oeuvre, which ranged from the study of musical instruments and collecting to medieval art and the literature on art.